EVALUATION OF TRANSFECTED FIBROBLAST CELLS -OF SAHIWAL CATTLE FOR TRANSFECTION / NUCLEAR TRANSFER STUDIES - LAXMI, N ANAND; GUNJAN, G (The Indian Journal of Animal Reproduction, 2023)
The development of an efficient transfection system in livestock cells is an important step towardsinvestigating gene transfer and has impact mainly in agriculture and fundamental biology. Thedevelopmental capacity of transfected fibroblast cells isolated from skin piece of ear pinna of adultSahiwal cattle was studied. Effect of transfection and in vitro culture of cells for six successive passagespost transfection was evaluated. Important factors involved in cationic liposome mediated gene transferwere evaluated through in vitro transfection of bovine fibroblast cells. Transfection of plasmid DNAcomplex (pEGFP and DNAfectin reagent) was evaluated and standardized utilizing the parametersconcentration of DNA, lipofection reagent, cell density, and the effect of transfection time on theefficiency of indigenous Sahiwal cattle fibroblasts to express a reporter gene. Stable transfectionswere conducted using a green fluorescence protein (GFP) reporter plasmid containing the neomycinresistance gene.
Keywords: Transfection; Liposomes; Fibroblasts; Livestock cells